الصلح بديلاً للدعوى الجزائية في القانون الفلسطيني = Reconciliation as an alternative to criminal persecution in the Palestinian law = Perdamaian sebagai altenatif kepada pendakwaan jenayah dalam undang-undang Palestin - Elshobake, Mohammed Rafiq Mu'Min; Negasi, Mohamed Ibrahim; Laeba, Muhammad (IIUM Press, International Islamic University Malaysia, 2018)
تـُ عتـُعَدُّ الدعوى الجزائية الوسيلة القانونية العادية للفصل في المنازعات الجنائية، غير أن الاقتصار عليها كثير ً ا في فلسطين أدَّ ى إلى وقوع أزمات طالت العدالة الجنائية؛ نتيجة تراُكُم الدعاوى الجنائية المنظورة أمام القضاء الفلسطيني، بالإضافة إلى إشكاليات عدة في تطبيق العقوبات على ا رمين؛ أبرزها أن لا مراكز إصلاح وتأهيل (سجون) ملائمة إصلاح ا رمين؛ لذا كان لا ببُدَّ من العمل على تطبيق وسائل بديلة لحل المنازعات الجنائية تُعرف بـ(بدائل الدعوى الجنائية)، ومن أهمها الصلح الجنائي، ويُناقش هذا البحث ماهية الصلح الجنائي وطبيعته ونطاقه وآثاره وموقف المشرع والقضاء الفلسطيني منه، وذلك باتباع المنهج الاستقرائي، ويخلص هذا البحث إلى أن القانون الفلسطيني اكتفى بالنص على نظام الصلح الجنائي في جرائم الشيك، وأن القضاء الفلسطيني يأخذ بالمصالحة بين طرفي النزاع سببً ا من أسباب تخفيف العقوبة ومسوغًا لقبول طلبات الإفراج بكفالة . ************************** Criminal proceeding is the normal legal method to resolve criminal disputes save it for the situation in Palestine where exclusively depending on it might result in crisis that would delay justice due to the backlog cases to be handled by the Palestinian judiciary. This is in addition to numerous dilemma in executing punishments on the criminals due to the absence of proper rehabilitation facility for the criminals. This had prompted to alternative methods to resolve criminal disputes known as alternative criminal proceedings. Among these methods are criminal reconciliation. This paper discusses its definition, nature, scope, effects and the position of Palestinian legislators and judiciary on it. This is done by following the deductive method. In conclusion the paper finds that the Palestinian Legislature had sufficed to mention criminal reconciliation procedure in cheque related crimes; the Palestinian judiciary take into consideration the interest of the disputing parties as a basis to mete out lighter punishment and a reason to consider application to release the defendants through bail. ************************ Prosiding jenayah adalah kaedah undang-undang yang biasa untuk menyelesaikan pertikaian jenayah untuk keadaan di Palestin yang bergantung kepada krisis yang akan melambatkan proses keadilan akibat kes-kes tertunggak yang akan ditangani oleh badan kehakiman Palestin. Tambahan lagi, banyak dilema dalam melaksanakan hukuman terhadap penjenayah kerana tidak adanya kemudahan pemulihan yang betul untuk penjenayah. Ini telah mendorong kepada kaedah alternatif untuk menyelesaikan pertikaian jenayah yang dikenali sebagai prosiding jenayah alternatif. Antara kaedah ini ialah perdamaian. Artikel ini membincangkan definisi, ciri, skop, kesannya dan kedudukan ahli perundangan dan kehakiman Palestin menggunakan kaedah deduktif. Kesimpulannya, kajian ini mendapati bahawa Badan Perundangan Palestin telah cukup untuk menyebut prosedur perdamaian jenayah dalam jenayah berkaitan cek; Badan Kehakiman Palestin mempertimbangkan kepentingan parti yang bersengketa sebagai dasar untuk melaksanakan hukuman ringan dan alasan untuk mempertimbangkan permohonan untuk membebaskan defendan melalui jaminan.